Cannibalism, survival and growth performance of juvenile African catfish Clarias gariepinus in relation to photoperiod and 17β‐Oestradiol treatment. (14th June 2022) - Indriastuti, Cecilia Eny; Junior, Muhammad Zairin; Suprayudi, Muhammad Agus; Supriyono, Eddy; Alimuddin, Alimuddin
Abstract: This study evaluated the survival rate (SR), cannibalism, and growth performance in juveniles African catfish reared in photoperiod conditions and administered with different doses of 17β‐oestradiol (E2 ). A completely randomized design was used with four replicates in a 3 × 2 factorial, three photoperiods (24L:0D, 12L:12D, 0L:24D) and two levels of E2 in the diet (0 and 50 mg kg −1 ). Fish fed a diet containing 50 mg kg −1 of E2 and (0L:24D) significantly showed greater survival. The highest cannibalism level and type‐1 cannibalism were obtained in the photoperiod of 12L:12D and the lowest in fish fed with the inclusion of the E2 . The highest non‐cannibalism mortality was obtained in animals fed with the inclusion of the E2 . The highest potential of cannibalism was shown fish fed without the inclusion of E2 . Fish fed a diet containing of E2 had the lowest defect. The highest SGR, LG, WG and FUE were demonstrated by the treatment (0L:24D) and in fish fed with the inclusion of the E2 . Higher glucose levels were demonstrated in fish submitted to the 12L:12D photoperiod fed the diet without E2 inclusion. Administration of E2 resulted in high levels of 17β‐oestradiol in the body of the catfish under the 24L:0D and 0L:24D. Testosterone in the body of juvenile catfish decreased due to the administration of E2 at the 0L:24D condition. Juvenile catfish reared at high densities under the 0L:24D photoperiod and addition 50 mg kg −1 of E2 showed the lowest cannibalism level and greater survival and growth.